Carbon monoxide poisoning during pregnancy treated with hyperbaric oxygen. Issue 5 (5th May 2021) - Kosaki, Yoshinori; Maeyama, Hiroki; Nojima, Tsuyoshi; Obara, Takafumi; Nakao, Atsunori; Naito, Hiromichi
Abstract: Acute carbon monoxide (CO) intoxication during pregnancy causes fetal death and teratogenic effects. Hyperbaric oxygen (HBO2) therapy has the potential to improve them. HBO2 therapy should be considered to treat CO intoxication during pregnancy. Abstract : Acute carbon monoxide (CO) intoxication during pregnancy causes fetal death and teratogenic effects. Hyperbaric oxygen (HBO2) therapy has the potential to improve them. HBO2 therapy should be considered to treat CO intoxication during pregnancy.